Catheter-Based Computer Tomography Angiography in Double-Skin Paddle Anterolateral Thigh Perforator. Issue 2 (February 2021) - Pang, Xiaoyang; Qing, Liming; Wu, Panfeng; Tang, Ju-yu
Abstract : Supplemental digital content is available in the text.